Gelling and storage performance of surimi prepared from some tropical fish - Hassan, Femeena; Mathew, Saleena; Mukundan, M K (Indian Journal of Fisheries, 2011)
Surimi is base for a variety of food formulations. Physico-chemical, organoleptic and microbiological changes taking place in surimi prepared from four tropical fishes, common carp (Cyprinus carpio), tilapia (Oreochromis mossambicus), threadfin bream (Nemipterus japonicus) and shark (Scoliodon sorrakowah) during frozen storage are discussed. The compressibility of shark surimi was more compared to other species. Its organoleptic and physical qualities were good even after a year's storage. Microbiological parameters showed insignificant variation between samples.